AGGRESSION ON KOSOVO BETWEEN MEDIA CONSTRUCTION AND REALITY - Stanković Pejnović, Vesna (Politeia, 2021)
Aggression against Kosovo is an example of how the NATO and the ‘international community’ have (mis)used Serbia and Kosovo in a classic modern exercise of identity construction by disciplining the Balkan ‘other’. The discourse of security is not a neutral academic terrain, but a continuous struggle for political power, access to resources, and the authority to articulate new definitions and priorities of security. Modern reasons for war were absent because the conflict in Kosovo centered around the pursuit of moral aims (rather than traditional politics) by other means. The vocabulary employed related more to the tradition of a just war (a notion that preceded the era of modern wars), which was firmly grounded in denationalization and aimed to replace politics with the imperative of universal principles and virtue. The aim of the paper is to show that the Kosovo model of aggression, behind the discourses of moral goals, traditionally political, has aimed to implement the new world order of imperialist powers under the auspices of the ‘international community’ and to establish full control over natural resources.